CARTILAGINOUS FISHES AND FISHERIES IN THE MEDITERRANEAN COAST OF TURKEY - Basusta, Nuri; Basusta, Asiye; Ozbek, Elif Ozgur (Turkish Marine Research Foundation-Tudav, 2016)
[Abstract Not Available]
Keywords: Guitarfish Rhinobatos-Rhinobatos; Length-Weight Relationships; Stingray Dasyatis-Pastinaca; Iskenderun Bay; Common Guitarfish; 1St Record; Reproductive-Biology; Trawl Fisheries; Gravid Female; Antalya Bay